Trilobatin, a Natural Food Additive, Exerts Anti-Type 2 Diabetes Effect Mediated by Nrf2/ARE and IRS-1/GLUT2 Signaling Pathways - Shi, Yan-Ling; Zhang, Yue-Ping; Luo, Huan; Xu, Fan; Gao, Jian-Mei; Shi, Jing-Shan; Gong, Qi-Hai (Frontiers in Pharmacology, 2022)
Oxidative stress and aberrant insulin signaling transduction play vital roles in type 2 diabetes mellitus (T2DM). Our previous researches have demonstrated that trilobatin (TLB), derived from the leaves of Lithocarpus Polystachyus (Wall.), exhibits potent antioxidative profile. In current study, we investigated the anti-T2DM effect of TLB on KK-Ay diabetic mice, and further to explore the potential mechanism. Our results showed that TLB not only significantly reduced high fasting blood glucose (FBG) level and insulin resistance, but also promoted the tolerances to exogenous glucose and insulin in KK-Ay mice. Moreover, TLB reduced the content of reactive oxygen species, enhanced antioxidant enzymes activities including serum catalase, glutathione peroxidase and superoxide dismutase, and regulated the abnormal parameters of lipid metabolism including triglyceride, high density lipoprotein-cholesterol, low density lipoprotein-cholesterol and free fatty acid, as evidenced by enzyme-linked immunosorbent assay. Additionally, TLB markedly ameliorated the pancreatic islet morphology near normal and increased the insulin expression of islet. Whereafter, TLB promoted Nrf2 translocated from cytoplasm to nucleus; moreover, it also increased the protein expressions of HO-1, NQO-1 and GLUT-2, and phosphorylation levels of Akt and GSK-3βSer 9; decreased the protein expressions ofkeap-1, and phosphorylation levels of IRS-1Ser 307 and GSK-3βTyr 216. Taken together, our findings reveal that TLB exhibits anti-T2DM effect in KK-Ay mice by activating the Nrf2/ARE signaling pathway and regulated insulin signaling transduction pathway, and TLB is promising to be developed into a novel candidate for treatment of T2DM in clinic due to its favourable druggability.